Digital tools and agricultural market transformation in Africa: Why are they not at scale yet, and what will it take to get there? - Abate, Gashaw T.; Abay, Kibrom A.; Chamberlin, Jordan; Kassim, Yumna; Spielman, David J.; Tabe-Ojong, Martin Paul (Elsevier, 2023)
Despite enthusiasm for the potential of digital innovations to transform agricultural markets in Africa, progress made thus far has been limited to small-scale experiments that often fail to scale up. Realizing the full potential of digital innovations – tools, technologies, applications, and services – in Africa requires not just further development of these solutions at meaningful scales, but also more nuanced evidence from both successful and unsuccessful scaling efforts. This paper reviews the conceptual and empirical evidence on the transformative potential of digital innovations for African agricultural markets with an in-depth examination of solutions that have been rolled out to date in the continent. Specifically, the review addresses the following questions: (i) how can digital innovations improve the functioning of agricultural markets in Africa? (ii) what explains the apparent disconnect of most pilots to scale-ups? (iii) what is required to realize their full potential? and (iv) what are the emerging risks and opportunities associated with digital innovations for agricultural marketing? Although our review of the landscape and literature on market-focused digital innovations in Africa identifies several reasons to remain optimistic, the prevailing disconnect between pilots and scale-ups merits further evaluation. In particular, there is a need for more systematic assessments of both successes and failures at both the piloting and scaling stages.